Bony increased-offset reverse shoulder arthroplasty: A meta-analysis of the available evidence. (February 2021) - Dimock, Richard; Fathi Elabd, Mohamed; Imam, Mohamed; Middleton, Mark; Godenèche, Arnaud; Ali Narvani, A
Background: Reverse shoulder arthroplasty (RSA) has revolutionized the management of many shoulder pathologies. Lateralization has become favourable to combat complications (e.g. notching, compromised external rotation), using a metallic, or autogenous bone-graft baseplates – bony increased-offset reverse shoulder arthroplasty (BIO-RSA). We systematically reviewed the literature to determine: Does BIO-RSA improve range of motion and outcome scores? Are notching rates decreased? Does the graft heal? Methods: All available prospective studies, trials and case series reporting on BIO-RSA were included. Outcomes were grouped into outcome scores, range of motion and radiographic outcomes. Data were pooled and statistical analysis performed. Results: Eight studies reported on 385 RSA – 235 BIO-RSA and 150 standard-RSA (STD-RSA). Follow-up was 20–36 months; average age 74 years. Outcome scores: Constant-Murley and SSV scores showed statistically significant post-operative benefit of BIO-RSA (mean-difference 4.0 (95% confidence interval (CI): 0.79, 7.1) and 6.8 (95% CI: 3.8, 9.9)). No Minimal Clinically Importance Difference was surpassed. Range of motion: No difference was found in any direction. Notching: Notching was less likely with BIO-RSA (odds ratio 0.19 (95% CI: 0.10, 0.38)). Healing and loosening: 92% grafts fully healed/incorporated. Loosening rate was 2.4%. Conclusions: Literature on BIO-RSA is limited with only one randomised controlled trial (RCT). Weak evidence exists for improved outcome scores. Range of motion is equivocal. Notching rates are significantly lower in BIO-RSA. The graft usually heals.